Single Stage Shrinkage Estimation Methods for Reliability Function of Generalized Exponential Distribution Using Simulation - Ahmed, Isaam Kamel; Taha, Taha Anwar; Salman, Abbas Najim (Iraqi Journal of Science, 2024)
The reliability in stress–strength model (s–s) is estimated in this article when the system has parallel and series components subject to one of the stresses and it follows generalized exponential distribution by taking via different estimation methods, namely the maximum likelihood estimation, unbiased estimation, moment estimation and shrinkage estimation. Also, the Mont Carlo method is used to compare these methods under mean squared error.